Planning documentation based pre-use phase LCA of a new urban area in New Skerjafjörður, Reykjavík - Hjördís Sóley Sigurðardóttir 1976- (2022)
The built environment has been identified as being responsible for causing significant environmental impacts, which indicates the opportunity for the sector to be of great importance in the battle against environmental problems. The main strategy today has been on urban density for lowering greenhouse gas emissions from housing and transport as well as studying the emissions caused by buildings with life-cycle assessment (LCA). However, the holistic approach seems to be missing, where environmental goals in the planning stage with the development of buildings are connected. This thesis expands the common use of LCA on buildings and proposes the method on a neighborhood scale for reaching a holistic approach. The thesis aims to identify opportunities for how LCA can be used for improving environmental impacts when designing and for decision-making in the planning stage. The study focuses on the pre-use phase because that phase has proven to cause a significant spike in carbon emissions when considering the near future and is crucial in reaching climate change goals. The study case is a new neighborhood plan in New Skerjafjörður, Reykjavík. The assessment focuses on the environmental impacts of the neighborhood, considering buildings and other spaces needed to build up a new neighborhood. The thesis identifies material to use as a key factor in the design stage. It demonstrates how the total emissions of climate change in the neighborhood are reduced when more environmentally friendly materials are replaced by traditional ones. It reduces GHG emissions by up to 40% in total as well as it reduces emissions in most of the other documented environmental categories.